Genomic abnormalities of TP53 define distinct risk groups of paediatric B-cell non-Hodgkin lymphoma - Newman, Alexander M; Zaka, Masood; Zhou, Peixun; Blain, Alex E; Erhorn, Amy; Barnard, Amy; Crossland, Rachel E; Wilkinson, Sarah; Enshaei, Amir; De Zordi, Julian; Harding, Fiona; Taj, Mary; et al. (Leukemia, 2022)
Children with B-cell non-Hodgkin lymphoma (B-NHL) have an excellent chance of survival, however, current clinical risk stratification places as many as half of patients in a high-risk group receiving very intensive chemo-immunotherapy. TP53 alterations are associated with adverse outcome in many malignancies; however, whilst common in paediatric B-NHL, their utility as a risk classifier is unknown. We evaluated the clinical significance of TP53 abnormalities (mutations, deletion and/or copy number neutral loss of heterozygosity) in a large UK paediatric B-NHL cohort and determined their impact on survival. TP53 abnormalities were present in 54.7% of cases and were independently associated with a significantly inferior survival compared to those without a TP53 abnormality (PFS 70.0% vs 100%, p < 0.001, OS 78.0% vs 100%, p = 0.002). Moreover, amongst patients clinically defined as high-risk (stage III with high LDH or stage IV), those without a TP53 abnormality have superior survival compared to those with TP53 abnormalities (PFS 100% vs 55.6%, p = 0.005, OS 100% vs 66.7%, p = 0.019). Biallelic TP53 abnormalities were either maintained from the presentation or acquired at progression in all paired diagnosis/progression Burkitt lymphoma cases. TP53 abnormalities thus define clinical risk groups within paediatric B-NHL and offer a novel molecular risk stratifier, allowing more personalised treatment protocols.
Keywords: Gene Dosage; Genetic Loci; Male; mutace; genetické lokusy; Child, Preschool; progrese nemoci; Adolescent; Infant; Child; genová dávka; Lymphoma, B-Cell; dítě; B-buněčný lymfom; mužské pohlaví; Disease Progression; nádorový supresorový protein p53; mladiství; předškolní dítě; lidé; ženské pohlaví; Humans; kojenec; Mutation; Female; Tumor Suppressor Protein p53